AKURASI ARAH KIBLAT MUSALA STASIUN PENGISIAN BAHAN BAKAR UMUM (SPBU) DI KOTA MAKASSAR - Muhammad Ridha Muslih; Rahma Amir (Universitas Islam Negeri Alauddin Makassar, 2020)
This research is classified as qualitative field research, with the research approaches used are syar'i approach and astronomical approach. The data source in this study is the primary data source, which is obtained from the results of observations and interviews conducted at the Rappocini gas station, Makassar City, while the secondary data sources in this study are obtained from books, journals, theses, and scientific writings related to the object of research. . Furthermore, the data collection methods used in this study were observation, interviews, and documentation. In data processing, this study was carried out in four stages, namely: data summarization (reduction), data presentation, conclusion and verification, and final conclusions. The method used by petrol stations in determining the direction of the Qibla of the Musala is to use a software-based android cellphone, and following the position of the nearest mosque Qibla direction around the Musala gas station, the rest only follows the direction of the Qibla in general. Both methods cannot be used as a basis in determining the direction of the Musala Qibla at gas stations. Based on the results of observations on the accuracy of the Qibla direction of the SPBU Musala, the data obtained were: namely Musala SPBU 74,902.02 Jalan Hertasning, Kassi-Kassi Village, the old Qibla direction was 276 ° off of 16 °, Musala SPBU 74,902.50 Jalan Aroepala, Karunrung Village had the right direction of the Qibla, Musala SPBU 74.902.25 Jalan Pengayoman Rappocini Village, the old qibla direction is 267 ° off 25 °, Musala SPBU 74.902.31 Jalan AP Pettarani, Buakana Village, the old qibla direction is 280 ° off of 12 °.